2014
DOI: 10.1523/jneurosci.1572-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Dysfunction of the Thrombospondin Receptor α2δ-1 Underlies the Overeating and Obesity Triggered by Brain-Derived Neurotrophic Factor Deficiency

Abstract: Brain-derived neurotrophic factor (BDNF) and its receptor, TrkB, are critical components of the neural circuitry controlling appetite and body weight. Diminished BDNF signaling in mice results in severe hyperphagia and obesity. In humans, BDNF haploinsufficiency and the functional Bdnf Val66Met polymorphism have been linked to elevated food intake and body weight. The mechanisms underlying this dysfunction are poorly defined. We demonstrate a chief role of ␣2␦-1, a calcium channel subunit and thrombospondin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 62 publications
(16 reference statements)
3
26
0
Order By: Relevance
“…This observation was surprising considering our previous finding that rescuing an α2δ-1 deficit broadly in the VMH of adult mice with central BDNF depletion mitigated their hyperphagic behavior and obesity (Cordeira et al, 2014). There are several potential explanations for this discrepancy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This observation was surprising considering our previous finding that rescuing an α2δ-1 deficit broadly in the VMH of adult mice with central BDNF depletion mitigated their hyperphagic behavior and obesity (Cordeira et al, 2014). There are several potential explanations for this discrepancy.…”
Section: Discussionmentioning
confidence: 77%
“…Our previous investigations suggested a role of alpha2delta-1 (α2δ-1) in energy and glucose balance control acting downstream of brain-derived neurotrophic factor (BDNF) in the VMH (Cordeira et al, 2014). BDNF signals through the tyrosine kinase B (TrkB) receptor to support neuronal survival, differentiation, and synaptic plasticity (Reichardt, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While future investigation on these neurons is needed, we directed a research effort in this work to BDNF-expressing neurons, because previous reports have pointed out that administration of GABA receptor antagonist can increase BDNF in several brain regions (Enna et al, 2006; Heese et al, 2000), and besides, BDNF is expressed in the VMH and PVN of hypothalamus and masterly regulates feeding behavior and energy homeostasis (An et al, 2015; Cordeira et al, 2014), while our results in Figure 5 revealed that astrocytic IKKβ/NF-κB activation remarkably rendered many neurons in these two subregions to be more responsible to GABA. We questioned if BDNF neurons in these subregions might be partially responsible for feeding and body weight in the same line as the effect of GABA manipulation.…”
Section: Resultsmentioning
confidence: 99%
“…Boulac reported a dose-dependent weight gain as well, over 6 months of treatment in large open-label study involving 610 patients [130]. Weight gain associated with gabapentin is related to overeating and increased appetite, possibly due to central mechanisms on hypothalamic pathways [131]. Even though there are no reports on the risk of gabapentin and fatty liver or visceral obesity, it is relevant that gabapentin is commonly prescribed for peripheral neuropathy occurring as a complication of diabetes.…”
Section: Management Of Seizuresmentioning
confidence: 99%